Proceedings of the 5th International Conference on Information Engineering for Mechanics and Materials 2015
DOI: 10.2991/icimm-15.2015.113
|View full text |Cite
|
Sign up to set email alerts
|

FeCoNiAlTiCrSi high entropy alloy coating prepared by laser cladding

Abstract: Abstract.A FeCoNiAlTiCrSi high entropy alloy coating was cladding on the surface of Q235 steel by laser using FeCoNiAlTiCrSi as basic alloy powder in which B, C, and Y 2 O 3 were added as a in situ synthesized elements. The results show that the 2mm thickness coating with no crack and pores was prepared under the optimized laser process parameters that the power is 1380W, spot size is 6mm × 4mm, scanning speed is 6mm/s, overlapping rate is 36% and shielding gas velocity is 1.5L/min. The structure is mainly com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The new-type high-entropy alloy material is the ideal laser cladding material, which has the excellent weldability, machinability, and strength toughness due to the unique four effects of the high-entropy effect, lattice distortion effect, slow diffusion effect, and cocktail effect [5][6][7][8][9][10][11][12], revealing outstanding advantages in surface modification, which has attracted many researchers' attention [13][14][15][16][17][18][19]. Qiu et al [13] successfully prepared Al 2 CrFeCo x CuNiTi high-entropy alloy coating with good molding quality on the surface of Q235 steel by using laser cladding technology, taking laser power of 2500 W and scanning speed of 3 mm/s as the process parameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new-type high-entropy alloy material is the ideal laser cladding material, which has the excellent weldability, machinability, and strength toughness due to the unique four effects of the high-entropy effect, lattice distortion effect, slow diffusion effect, and cocktail effect [5][6][7][8][9][10][11][12], revealing outstanding advantages in surface modification, which has attracted many researchers' attention [13][14][15][16][17][18][19]. Qiu et al [13] successfully prepared Al 2 CrFeCo x CuNiTi high-entropy alloy coating with good molding quality on the surface of Q235 steel by using laser cladding technology, taking laser power of 2500 W and scanning speed of 3 mm/s as the process parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Qiu et al [13] successfully prepared Al 2 CrFeCo x CuNiTi high-entropy alloy coating with good molding quality on the surface of Q235 steel by using laser cladding technology, taking laser power of 2500 W and scanning speed of 3 mm/s as the process parameter. Guo et al [14] successfully prepared an FeCoNiAlTiCrSi high-entropy alloy coating on the surface of Q235 steel using laser cladding technology. The results showed that under the optimized laser process parameters of 1380 W power, scanning speed of 6 mm/s, overlap rate of 36%, and protective gas velocity Coatings 2023, 13, 1744 2 of 9 of 1.5 L/min, the high quality FeCoNiAlTiCrSi coating with a thickness of 2 mm and no cracks and pores was prepared.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this unique combination of the properties and the potential for designing a wide variety of new materials, interests have been directed toward high entropy alloy films and coatings for applications where corrosion and oxidation protection are strongly required. This is a new field of research, and till now, HEA coatings have been produced by magnetron sputtering [11], laser cladding [12], thermal spraying [13], and only very few examples were produced by electrodeposition [10,[14][15][16][17]. Electrodeposition of HEA is challenging due to the complexity of the electrolyte bath with multiple metallic precursors and the sensitivity of the deposition parameters on co-depositing multiple metals.…”
Section: Introductionmentioning
confidence: 99%